Pendampingan Belajar Matematika Pada Materi Perkalian Menggunakan Media Pembelajaran Kincir Perkalian - Danial Danial; Suci Triana; Syarifuddin Syarifuddin (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIM Sinjai, 2025)
This service aims to introduce students to the multiplication wheel media and help students improve their knowledge and skills in the learning process so that students do not get bored when studying Mathematics. This service was carried out at SDN 213 Sabbang where teachers still had minimal use of learning media. The learning media used is the multiplication wheel media. The aim of this research is to increase students' understanding of the concept of multiplication operations using the multiplication pinwheel media method. The results of the activity show that the use of appropriate instructional media can increase students’ enthusiasm for learning multiplication. The multiplication wheel media not only helps students understand the concepts more concretely but also creates a more engaging and interactive learning atmosphere. In addition, based on the findings during the community service program, it is recommended that teachers create varied learning situations in the classroom, not rely solely on textbooks, and utilize relevant and creative learning media to enhance the effectiveness of mathematics instruction. These efforts are expected to continue supporting the improvement of teaching and learning quality in elementary schools.